PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL DRILLING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 2 TANAH PUTIH ROKAN HILIR - Maila Juhernita; Betty Holiwarni; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aims to increase student learning achievement on the subject structure of atoms and the periodic system of elements in class X SMAN 2 Tanah Putih Rokan Hilir. This research was of experiment research with pretest-posttest design. The research was conducted in SMAN 2 Tanah Putih Rokan Hilir. The samples of this research were the students of class X5 as the experimental class and students of class X4 as the control class. In experimental class was applied cooperative learning type Snowball Drilling model, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tcount>ttable is 4,98 > 1,67, means that the application of model cooperative learning type Snowball Drilling can improve student achievement on the subject structure of atoms and the periodic system of elements in class X SMAN 2 Tanah Putih increase learning achievement category in the experimental class is based on the normalized gain score (N-Gain) relatively high at 0,84.Keywords: Cooperative Learning, Snowball Drilling, LearningAchievement, Atomic Structure and Element of the Periodic System.